Assessment on the Conditions of Persons Under Custodial Facility (PUPC) during Covid-19 Pandemic - Isidro, Rod Marc; Nedic, Jason O.; Panambo, Sheryl D.; Tarroza, Elyca; Villa, Elizabeth Buena (Future Science / FSH-PH Publications, 2024)
This study aimed to assess the conditions of persons under custodial facility in Laguna Police Station during Covid-19 pandemic in Laguna Province. This study employed the use of descriptive comparative utilizing survey methodology. Research locale was limited a Police Custodial Facility in Laguna Province. The respondents were the 10 police officers and 10 persons in custody facility and were selected using purposive sampling technique. The research instrument in this study was a survey questionnaire adopted from the guidelines and procedures in the management and supervision of all PNP custodial facility and persons under PNP custody. Data were analyzed using mean, and One Way Analysis of Variance. The study found that the custody facility in the Philippines has maintained good conditions, with both police officers and persons in custody rating the implementation as moderate. The facility effectively implemented protocols to protect its personnel and those under its control, preventing the transmission of the virus. However, there is a significant disparity in evaluations, indicating structural flaws in the criminal justice system. To address these issues, a comprehensive strategy focusing on openness, responsibility, and the perspectives of those directly affected by correctional circumstances is needed. Cooperation among various actors, including communities, government authorities, civil society groups, and law enforcement agencies, is crucial. Independent oversight measures and accountability from human rights commissions and civil society groups can ensure compliance with human rights norms.